PENGARUH EKUITAS MEREK, KUALITAS PRODUK DAN IKLAN TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE MEREK SAMSUNG (STUDI KASUS MAHASISWA/I UNIVERSITAS GUNADARMA) - Taat Kuspriyono (Universitas Bina Sarana Informatika, 2016)
The purpose of this study was to analyze the Effect Of Brand Equity, Quality Products And Advertising On The Decision To Purchase Brand Smartphone Samsung (Case Study Students / I University Gunadarma). This type of research is quantitative. The data source of this research is the primary data take samples samsung customers. Data is collected using accidental sampling with customers spread to 98 respondents. This study uses multiple regression analysis. Result the findings of this study indicate that: (1) Brand Equity significantly affect Decision To Purchase Brand Smartphone Samsung (2) Quality Products significant effect on Decision To Purchase Brand Smartphone Samsung (3) Advertising significantly influence Decision To Purchase Brand Smartphone Samsung (3) Brand Equity, Quality Products And Advertising significantly influence Decision To Purchase Brand Smartphone Samsung Keywords: Quality of Web Information Service Quality Online and Corporate Image